Improving Nutrition Services to Reduce Plate Waste in Patients Hospitalized Based on Theory of Constraint - Thinni Nurul Rochmah (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Highly plate waste in hospitalized patients has become a problem in Hospitals’ nutrition service department, this causes adding treatment time for patient’s recovery and making the hospital service inefficient.Objectives: This research strives to develop a set of recommendations to improve the nutrition department service quality by reducing plate wastes in hospitals. Methods: This research uses a cross-sectional approach. The constraint causing analysis is done by observing dominant waste in each menu’s component and conducting FGD with the management team, nutrition department, and other related departments. The research population is 3000 plates.Results: One of the success indicators in the hospital’s nutrition services is less than 20% of plate waste. It was found that 26,65% or 327 of 1230 observed plates have more than 20% plate waste. The constraint was set with low scale value, food’s aroma, with 2,7 which make food’s aroma as a first priority problem to solve.Conclusions: The solution recommendation about constraint causes was sent to the nutrition department and hospital directors to review the hospital’s policies and SOP. The improvement can be focused on the hospital’s internal policies, Standard Operating procedures, employee competencies, obedience to set procedures, and also chefs and cooks skill